Peran BUMDes dalam Pengembangan Pariwisata Berbasis Masyarakat di Desa Torongrejo Pasca Pandemi COVID-19 - Shiona, Altlya Elok Yearmil; Widianto, Ahmad Arif (Sekolah Vokasi, Universitas Gadjah Mada, 2023)
Community based tourism is one of the tourism development models that makes the community the main actors in its development. As an institution formed to empower the community, BUMDes Bejo has a business unit focused on tourism development. This research aims to elaborate on the role of BUMDes Bejo in developing community based tourism through the Banyu Rancang tourist attraction from its inception to the present. The research uses a qualitative descriptive research method with a case study approach. Data collection techniques in this research include observation, in-depth interviews, and documentation. The principles of Community Based Tourism (CBT) and Anthony Giddens' Structuration theory are used to analyze the results. The research results show that the role of BUMDes in developing community based tourism in Torongrejo Village is not optimal, attributed to the unclear BUMDes structure since the pandemic and a lack of suitable human resources to manage it. Despite BUMDes having a limited role in its development, Banyu Rancang tourism is still being developed with the support of the Torongrejo Village Government and the Batu City Tourism Office. Based on the significance, domination, and legitimacy structure in the development of Banyu Rancang tourism, it is concluded that several stakeholders involved, including tourism managers, youth organizations, the Torongrejo Village Government, and the Batu City Department of Tourism have played their roles well through the support and motivation given to advance Banyu Rancang tourism.